INTEGRASI PEMBELAJARAN BAHASA INGGRIS DAN MODAL SOSIAL DALAM PENGEMBANGAN EKONOMI DESA WISATA - Ade Isyana Hairunnisah; Afni Rosalina (STKIP Pesisir Selatan, 2026)
This study aims to analyze the management of English language learning and the role of social capital as a strategy for economic development in Liang Pemantang Tourism Village (Lau Mentar). Limited English communication skills among local communities remain a major challenge in improving service quality and competitiveness in rural tourism destinations. This research employed a qualitative approach using a case study design. The participants included tourism village managers, English learning facilitators, micro and small enterprise actors, and members of tourism awareness groups. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using an interactive thematic analysis technique. The findings reveal that participatory, contextual, and practice-based management of English language learning enhances community confidence in communicating with international tourists. The effectiveness of the program is strongly supported by social capital, particularly trust, social networks, and norms of mutual cooperation, which encourage active participation and sustainability. The novelty of this study lies in integrating English language learning management and social capital within the framework of community-based rural tourism economic development.